P75 Physical impairment and Frailty in Patients with Chronic Obstruction Pulmonary Disease (COPD). (19th November 2012) - Gale, NS; Albarrati, AM; Munnery, I; Munnery, M; Tal-Singer, R; Hubbard, R; Cockcroft, JR; Shale, DJ
Abstract : Background: COPD is a multi-system disease, which has been linked to premature physiological ageing. Recognised co-morbidities include increased risk of cardiovascular events and osteoporosis, loss of muscle mass, function and impaired quality of life (QoL). The Chronic Geriatric Assessment (CGA) has been used to measure impairments, frailty and predict outcomes in older individuals. We hypothesised that the CGA would be greater in COPD than comparator subjects, and would relate to physical function and QoL in patients with COPD. Methods: As part of the Assessment of Risk in Chronic Airways Disease Evaluation (ARCADE)* longitudinal study, 300 patients with COPD (149 male) and 50 (28 male) comparators free from respiratory disease were evaluated. In all subjects spirometry, BMI, handgrip, 6 minute walk distance (6MWD), timed up and go (TUG), and the CGA were determined. The CGA is a 20 item interviewer administered questionnaire, which quantifies, physical, functional, psychosocial and medical impairments, scored out of 61, higher scores indicate more impairment. Health-related QoL was measured in patients using the St George's Respiratory Questionnaire (SGRQ) and MRC breathless was recorded. Results: Patients and comparators were similar in age, gender and BMI, but differed in lung function, grip strength, 6MWD, TUG and all domains of the CGA (Table 1 ). There was no difference in gender for BMI and CGA score. In patients, the total CGA score related to FEV1% r= –0.187, handgrip r= –0.335, 6MWD r= –0.548, TUG r=0.506, MRC breathlessness r=0.351 and number of exacerbations per year r=0.313 (all p<0.05) but did not relate to age. Of these, stepwise multiple regression showed that 6MWD, TUG, handgrip and number of exacerbations per year predicted the total CGA score. All of the CGA impairment categories related to all domains of the SGRQ (p<0.001). Conclusion: The CGA, a measure of impairment and frailty, was greater in patients with COPD than comparators. The CGA related to physical function (handgrip, TUG, 6MWD) and QoL independent of age in patients. The use of the prognostic utility of the CGA in COPD is worthy of further study which will be addressed longitudinally by the ARCADE study. *(Funded by GlaxoSmithKline)